Association between daily alcohol consumption and serum alpha klotho levels among U.S. adults over 40 years old: a cross-sectional study - Meihua Jiang; Xiaoyan Tang; Peng Wang; Li Yang; Rui Du (BMC, 2023)
Abstract Background Klotho is a hormone considered to be an anti-aging biomarker. The relationships between daily alcohol consumption and serum klotho are mainly unknown. The purpose of this study is to assess the relationship between alcohol consumption and serum alpha klotho (α−klotho) levels in the U.S. Methods The data came from 11,558 participants aged ≥ 40 in the 2007−2016 National Health and Nutrition Examination Survey. Adults with reliable α−klotho plasma results were the target population. The self-report method was used to assess alcohol consumption. The relationship between daily alcohol intake and serum α−klotho levels was estimated using multivariable linear regression models. We also performed a stratified analysis of clinically important variables. Results The mean serum α−klotho level among the 11,558 participants was 843.82 pg/mL. After full adjustment, participants with current moderate and heavy alcohol intake had lower serum α−klotho levels than those who never alcohol intake (β =  − 62.64; 95% CI: − 88.86, − 36.43; P < 0.001; β =  − 81.54; 95% CI: − 111.54, − 51.54; P < 0.001, respectively). Furthermore, the stratified analysis indicated that the association was insignificant in individuals with cardiovascular disease, chronic kidney disease, or cancer. Conclusion Daily alcohol consumption was inversely associated with serum α−klotho levels among U.S. adults over 40 years old. However, individuals with cardiovascular disease, chronic kidney disease, or cancer found no such relationship.